2007
DOI: 10.1063/1.2770513
|View full text |Cite
|
Sign up to set email alerts
|

Scattering properties and scattering kernel based on the molecular dynamics analysis of gas-wall interaction

Abstract: The scattering behaviors of nitrogen molecules reflected at a platinum surface are studied by the molecular dynamics method for the gas-surface interaction. The platinum surface is assumed to physically adsorb xenon molecules. Distributions of molecular velocities after reflection are obtained for the impinging molecules with specified velocities within a small range. The scattering distribution shows a bimodal behavior consisting of diffuse reflection and a distribution shifting to the velocity distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Interaction of gas molecules with channel surface is described in terms of scattering kernel. For specific combination of gas and membrane material, the parameters of the kernel (and the scattering model itself) can be obtained from molecular dynamics trajectories computations [9,10,11]. The choice of the theoretical model to describe scattering in a number of problem appears to be fundamental.…”
Section: Problem Statementmentioning
confidence: 99%
“…Interaction of gas molecules with channel surface is described in terms of scattering kernel. For specific combination of gas and membrane material, the parameters of the kernel (and the scattering model itself) can be obtained from molecular dynamics trajectories computations [9,10,11]. The choice of the theoretical model to describe scattering in a number of problem appears to be fundamental.…”
Section: Problem Statementmentioning
confidence: 99%
“…[13], the Maxwell model, denoted as the extended Maxwell model throughout the paper, is able to produce the accurate reflected velocity distribution if the system is slightly nonequilibrium. When the incident gas molecules are in a highly nonequilibrium state, such as that in molecular beam experiments, none of the existing gas-wall interaction models performs well [14,16]. The majority of previous studies focused on the reflected molecular velocity distribution or the correlation between the incident and reflected molecular velocities.…”
Section: Introductionmentioning
confidence: 99%
“…For applications in high-speed rarefied gas, significant work has been conducted on model validation [15]. For micro-and nanoscale gas flows, considerate efforts have recently been put forth to evaluate the empirical models by comparing the predicted molecular velocity distribution functions with those obtained from molecular dynamics (MD) simulations in simple problems such as Couette shear flow and the Fourier thermal problem [13,14,16,17]. These studies have shown that when the incident gas molecules are not in an equilibrium state, the reflected velocity distribution predicted by Maxwell model cannot match well with MD results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accommodation coefficients can also be found by comparison with Monte Carlo [122,118] or Molecular Dynamics [123,124] calculations. The surface data may be imported via atomic force microscopy on a real surface [125] or may be generated according to the wall characteristics [124,123].…”
Section: Boundary Conditionsmentioning
confidence: 99%